HIF‐1α Expression as a Protective Strategy of HepG2 Cells Against Fatty Acid‐Induced Toxicity. Issue 6 (June 2014) - Yoo, Wonbaek; Noh, Kyung Hee; Ahn, Jae Hee; Yu, Ji Hee; Seo, Ji A.; Kim, Sin Gon; Choi, Kyung Mook; Baik, Sei Hyun; Choi, Dong Seop; Kim, Tae Woo; Kim, Hyo Joon; Kim, Nan Hee
ABSTRACT Free fatty acid‐induced lipotoxicity via increased endoplasmic reticulum (ER) stress and hepatocyte apoptosis is a key pathological mechanism of non‐alcoholic steatohepatitis. A role of hypoxia‐inducible factor 1α (HIF‐1α) in this process has been suggested, but direct evidence is lacking. Here, we used HepG2 cells as a model to study whether HIF‐1α can reduce palmitic acid‐induced lipotoxicity and ER stress. In HepG2 cells treated with 500 µM palmitic acid, HIF‐1α expression increased transiently, the decline was associated with increased cleaved caspase‐3 expression. Overexpression and knockdown of HIF‐1α decreased and exacerbated, respectively, palmitic acid‐induced lipoapoptosis. The overexpression also blunted upregulation of the ER stress markers, C/EBP homologous protein (CHOP) and chaperone immunoglobulin heavy chain binding protein (Bip), while the knockdown increased the level of CHOP. In line with this, CHOP promoter activity decreased following HIF‐1α binding to the CHOP promoter hypoxia response element. These results indicate that hepatocyte lipotoxicity is associated with decreased HIF‐1α expression. It also suggests that upregulation of HIF‐1α can be a possible strategy to reduce lipotoxicity in non‐alcoholic fatty liver disease. J. Cell. Biochem. 115: 1147–1158, 2014. © 2014 Wiley Periodicals, Inc.